THE IMPLEMENTATION OF SMALL GROUP TO IMPROVE STUDENTSâ ENGLISH SPEAKING (A CLASSROOM ACTION RESEARCH IN THE SIXTH GRADE STUDENTS OF ISLAMIC ELEMENTARY SCHOOL MIFTAHUL MUBTADIIEN ISLAMIYAH BANYAKAN KEDIRI IN THE ACADEMIC YEAR 2013/2014 - Vitasmoro, Pamadya (English Teaching Journal, 2015)
Speaking is one of the English skills which are taught at school. It means that English can be taught at Elementary school based on the needs of the school. In Elementary school, teacher teaches four language skills such as: listening, speaking, reading and writing to make students to be competence in English by mastering those four skills.The students of Islamic Elementary School Miftahul Mubtadiien Islamiyah Banyakan faced some problems of speaking, such as they are afraid of making mistakes, they are shy of speak with other students, and they are low in speaking ability. This study applied Classroom Action Research. The objectives of this study is to describe how small group can improve studentsâ English speaking of the sixthÂ grade students of Islamic Elementary School Miftahul Mubtadiien Islamiyah Banyakan, Kediri. In the sixth grade in which researcher found problem in the class and try to find the solution. The students of sixth grade students of Islamic Elementary School Miftahul Mubtadiin Islamiyah Banyakan Kediri. There are 28 students totally. There are divided into male and female. 12 students are male and 16 students are female. This was conducted in two cycles: the first cycle consists of three meetings and so was the second cycle. The result of the research shows that (1) small group could improve studentsâ speaking ability in term of raising studentsâ achievement in the case of (a) fluency, (b) accuracy (pronunciation and Intonation) (2) small group can improve class situation, in term of (a) studentsâ interaction when having and responding teacherâs questions, (b) being active in small group activities, (c) being more attentive to the speaking class, (d) and the absence of students who were late and went out during speaking class, and (e) the unobservable dominancy of the teacher.